Influences of Socio-Demographic Factors and Health Utilization Factors on Patient-Centered Provider Communication. Issue 7 (3rd July 2018) - Singh, Shipra; Evans, Na'Tasha; Williams, Monica; Sezginis, Nilgun; Baryeh, Nana Ama Kwarteng
ABSTRACT: Patient-centered care has been documented as a measure of quality of health care and has been associated with positive health outcomes. However, the effect of health utilization on improving patient-centered communication has not been investigated. This study examined the effect of three important kinds of health utilization: routine check-up, frequency of provider visits in the last year, and quality of health care to patient-centered provider communication. Cross-sectional data from 3, 608 respondents to Health Information National Trends Survey-Cycle 4 2014 were analyzed. Multiple regressions were used to examine the association of sociodemographic factors and health utilization to patient-centered provider communication. Results showed that adults above 50 years and women reported higher patient-centered provider communication. Hispanic and Asian versus White respondents reported poorer patient-centered provider communication. Respondents with routine checkups between 1 and 2 years, 2 and 5 years, 5 or more years and none were all negatively associated with patient-centered provider communication in comparison with routine checkup within 1 year. Respondents who didn't visit health provider within past year had poorer patient-centered provider communication when compared to those who visited once. Finally, higher quality of healthcare experience was associated with higher patient-centered provider communication. Thus, this study highlights that race and ethnicity, age, and gender are significant factors that influence patient-centered provider communication; and specifically higher quality of healthcare experience, one provider visit within past year, and annual routine checkup as measures of health utilization predicts improved patient-centered provider communication.